Evaluation of polyaniline-Nafion® composite membranes for direct methanol fuel cells durability tests. (6th July 2015) - Escudero-Cid, R.; Montiel, M.; Sotomayor, L.; Loureiro, B.; Fatás, E.; Ocón, P.
Abstract A Nafion® membrane has been both electrochemically and chemically modified in-situ to incorporate polyaniline (PANi) into its structure. The proposed objective was to decrease the methanol (MeOH) permeability and thus improve the durability of a direct methanol fuel cell device. Permeability and conductivity of the modified membranes were measured using the unmodified Nafion® 117 as a reference. The permeability was determined from the electrochemical oxidation of permeated methanol, and the conductivity was determined via electrochemical impedance spectroscopy. To evaluate the effect of these modifications, the performance of a MeOH/O2 single-cell was measured using different MeOH flows and concentrations. The device durability was evaluated under a constant potential and at different operating times. The power density, p, at high MeOH flows and concentrations was 7 times higher for the PANi-modified membrane than the unmodified Nafion® 117. The durability of the modified membranes containing small amounts of PANi was 2 times higher using low MeOH flows and concentrations, while the power densities were similar. Impedance measurements were performed before and after the long-term durability tests in order to identify the improvements at the different parts of the fuel cell.